Sesquiterpene volatile organic compounds (VOCs) are markers of elicitation by sulfated laminarine in grapevine - Chalal, Malik; Winkler, Jana B.; Gourrat, Karine; Trouvelot, Sophie; Adrian, Marielle; Schnitzler, Jörg-Peter; Jamois, Frank; Daire, Xavier (Frontiers in Plant Science, 2015)
Inducing resistance in plants by the application of elicitors of defense reactions is an attractive plant protection strategy, particularly for grapevine (Vitis vinifera), which is susceptible to severe fungal diseases. Although induced resistance (IR) can be successful under controlled conditions, in most cases, IR is not sufficiently effective for practical disease control under outdoor conditions. Progress in the application of IR requires a better understanding of grapevine defense mechanisms and the ability to monitor defense markers to identify factors, such as physiological and environmental factors, that can impact IR in the vineyard. Volatile organic compounds (VOCs) are well-known plant defense compounds that have received little or no attention to date in the case of grape-pathogen interactions. This prompted us to investigate whether an elicitor, the sulfated laminarin (PS3), actually induces the production of VOCs in grapevine. An online analysis (proton-transfer-reaction quadrupole mass spectrometry) of VOC emissions in dynamic cuvettes and passive sampling in gas-tight bags with solid-phase microextraction-GC-MS under greenhouse conditions showed that PS3 elicited the emission of VOCs. Some of them, such as (E,E)-α-farnesene, may be good candidates as biomarkers of elicitor-IR, whereas methyl salicylate appears to be a biomarker of downy mildew infection. A negative correlation between VOC emission and disease severity suggests a positive role of VOCs in grape defense against diseases.